2016
DOI: 10.1080/17460441.2017.1268597
|View full text |Cite
|
Sign up to set email alerts
|

Designing small molecule CXCR3 antagonists

Abstract: IntroductionBy virtue of its specificity for chemokines induced in Th1-associated pathologies, CXCR3 has attracted considerable attention as a target for therapeutic intervention.Several pharmacologically distinct small molecules with in vitro and in vivo potency have been described in the literature, although to date, none have shown efficacy in clinical trials. Areas coveredIn this article I will outline the rationale for targeting CXCR3 and discuss the potential pitfalls in targeting receptors in poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…Recent studies demonstrated that therapy with potent smallmolecule CXCR3 antagonists showed significant efficacy in animal models of autoimmune diseases, including rheumatoid arthritis and multiple sclerosis, and in the prevention of transplant rejection. 3,[17][18][19] Cleavage of the transmembrane chemokines CXCL16 and CX3CL1 is associated with the inflammatory cascade and, therefore, the soluble form of the molecules may serve as inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that therapy with potent smallmolecule CXCR3 antagonists showed significant efficacy in animal models of autoimmune diseases, including rheumatoid arthritis and multiple sclerosis, and in the prevention of transplant rejection. 3,[17][18][19] Cleavage of the transmembrane chemokines CXCL16 and CX3CL1 is associated with the inflammatory cascade and, therefore, the soluble form of the molecules may serve as inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a CXCL10-antagonist demonstrated clinical efficacy in RA-patients [69]. CXCR3-antagnoists have shown promising results in vitro and in animal models but no clinical efficacy in psoriasis patients [70]. CCR5-inhibition, on the other hand, has been extensively studied in the context of HIV due to CCR5 being the entry receptor for HIV-1 [71,72].…”
Section: Blocking Infiltration To the Inflammatory Tissuementioning
confidence: 99%
“…CX3CL1, which is expressed on neurons, is pivotal to maintenance of immune quiescence ; the receptor is present in the CNS only on microglia ( 7 ). “Mucosal CKs” encompass CCL25, CCL28, CXCL14, and CXCL17 ( 37 ). “Angiogenic CKs” comprise many of the CXC CK family, such as CXCL1 through CXCL17 ( 38 ).…”
Section: Cks/cytokines and Their Receptorsmentioning
confidence: 99%